Morphometry and performance of Black Bengal goats at the rural community level in Bangladesh (Bangladesh Journal of Animal Science, 2013)
Data on morphometrics and performance of 106 Black Bengal goats were collected through an in-depth monitoring survey conducted in 73 families of Gangatia, Borachala and Pachpai villages of Bhaluka Upazila, Mymensingh, Bangladesh using a structured questionnaire. Analyses of variance were performed using the General Linear Model (GLM) procedure under Statistical Package for the Social Sciences (SPSS) version 14.0. Differences between mean values were separated using Duncuns Multiple Range Test (DMRT). Body weight of goats significantly (p